Safe spaces at festivals : a thematic analysis on how festival organisers and safe space managers in Aotearoa understand this service that they are providing : a thesis presented in fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University, Wellington, New Zealand - Bennett, Holly Siobhan (Massey University, 2023)
Safe Spaces are a supportive space provided by an event for people who seek help or require emotional assistance. They are a complex safety mechanism that is becoming increasingly commonplace at festivals globally, yet very little academic research has been conducted into what these spaces are, and their potential as a harm reduction service. Addressing this gap, the present study conducted 17 semi-structured individual and group interviews with festival organisers and managers of Safe Spaces at festivals in Aotearoa. These interviews were analysed with phenomenologically informed thematic analysis to explore how the participants understand this service they have chosen to provide. It was found that the creators of Safe Spaces understand them to be a site of active psychological intervention, situated within a dynamic and far reaching network of safety, and a complex, specialised, and world changing phenomena that evolves to meet the needs of the festival. A number of novel findings were produced related to their key operational elements, the adaptability and transferability of the service, and the role they play in individual and community mental health and well-being. Included in this write-up is a series of guidelines on what to consider when establishing a Safe Space service at a festival or event.
Keywords: 520304 Health psychology